1984
DOI: 10.1002/cne.902240408
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory cortical map changes following digit amputation in adult monkeys

Abstract: The cortical representations of the hand in area 3b in adult owl monkeys were defined with use of microelectrode mapping techniques 2-8 months after surgical amputation of digit 3, or of both digits 2 and 3. Digital nerves were tied to prevent their regeneration within the amputation stump. Successive maps were derived in several monkeys to determine the nature of changes in map organization in the same individuals over time. In all monkeys studied, the representations of adjacent digits and palmar surfaces ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
543
4
18

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,209 publications
(593 citation statements)
references
References 26 publications
28
543
4
18
Order By: Relevance
“…The findings indicate that SCI patients with DPS have greater sensitivity to somatosensory stimuli, particularly in skin areas with projections to We suggest that the cortical maps of deafferentated areas following SCI change similarly to the experimental demonstra tions of reorganization following amputa tion and deafferentation in monkeys. 29,44 The degree and quality of the reorganiza tion progressively changes over time and is influenced by pain and/or tactual stimula tion.46,47 The cortical representations of normally innervated skin surfaces, adjacent to the injured areas, slowly expand and occupy cortical territories that had previ ously represented the injured area. Accord ing to this view, it is reasonable to assume that innervated cortical regions in close proximity to deafferentated regions receive increased levels of stimulation causing more extensive reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that SCI patients with DPS have greater sensitivity to somatosensory stimuli, particularly in skin areas with projections to We suggest that the cortical maps of deafferentated areas following SCI change similarly to the experimental demonstra tions of reorganization following amputa tion and deafferentation in monkeys. 29,44 The degree and quality of the reorganiza tion progressively changes over time and is influenced by pain and/or tactual stimula tion.46,47 The cortical representations of normally innervated skin surfaces, adjacent to the injured areas, slowly expand and occupy cortical territories that had previ ously represented the injured area. Accord ing to this view, it is reasonable to assume that innervated cortical regions in close proximity to deafferentated regions receive increased levels of stimulation causing more extensive reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…There is no intrinsic, hard-wired, link between a location in a somatotopic map and a body location. This is especially true given Body Beyond SI 9 the clear plasticity of somatotopic maps following peripheral trauma (Merzenich et al, 1984;Pons et al, 1991) and learning Pascual-Leone & Torres, 1993). While some referral of sensation between skin surfaces may occur following massive cortical reorganisation (e.g., Ramachandran, Rogers-Ramachandran, & Stewart, 1992) or in plasticity induced by simultaneous tactile co-activation of skin surfaces (Schweizer et al, 2001;Sterr et al, 1998), in most cases plastic changes in somatosensory cortex do not lead to mislocalsation of touch.…”
Section: Localisation Of Touch On the Body Surfacementioning
confidence: 99%
“…Keywords: Back pain; Cortical reorganization; Magnetoencephalography; Source localization; Plasticity; Chronicity Research in animals [18,19] and humans [5,8,21] has shown that lesions of the afferent nerves may lead to extensive reorganization of the spinal and cortical zones that represent the deafferented body region. For example, in upper extremity amputees the cortical representation of the face was shown to 'invade' the representation of the hand and arm amputation zone [5,21] with the amount of reorganization observed being proportional to the magnitude of phantom limb pain [8].…”
Section: Introductionmentioning
confidence: 99%